Strategi Pengembangan Pendidikan Multikultural pada Institusi Pendidikan Islam - Yuli Supriani; Eko Budi Prasetyo; Uus Ruswandi; Mohamad Erihadiana (LP. Ma'arif Janggan Magetan, 2022)
The purpose of this study is to analyze the development strategy of multicultural Islamic education in Islamic educational institutions. He used the study of literature with a qualitative approach. Learning shows that: first, the foundation of multicultural Islamic Education Development consists of religious, historical, psychological, sociocultural, and geographical foundations. Second, Multicultural Islam The strategy of developing education in Islamic educational institutions can be pursued through two approaches, namely quantitative and qualitative. Quantitative development strategies are by socialization and internalization programs through scientific activities, multicultural educational innovation programs, and building a culture that accommodates the spirit and values of multiculturalism in the Islamic environment of the institution. Meanwhile, the qualitative development strategy is intensive in the Qur'an and Sunnah study programs, curriculum revision programs, education and training programs for educators, and local wisdom programs.